Of challenges of Inspection to educational changes - Estefanía Lera, José Luis (Avances en Supervisión Educativa, 2014)
The changes that occur in the XXI century entail the need for changes in the education system, among others, a competence approach to teaching; emphasis on learning, not only of individuals but also of educational institutions; more autonomy of schools; leadership and management culture of assessment and  continuous  improvement  teams.This new scenario also requires inspection focus towards improving the education system, and therefore the institutions and processes of teaching and learning as well as redefine the functions of supervision, control and guidance and to assert the role of assessment other functions assigned.In this context, the evaluation must be a shared responsibility between schools and the Administration, through processes internal or self-evaluation and external evaluation processes of schools conducted by the Inspectorate.
Keywords: educational inspection; evaluation; educational quality; autonomy of schools; educational improvement